Pengembangan Game Edukasi Crossword Puzzle untuk Meningkatkan Kemampuan Kognitif Pada Anak Kelompok B di TK IT Al-Fajar Mataram - Puji Indriani Sukma; Gunawan Gunawan; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2024)
This study aimed to develop an educational Crossword Puzzle game to effectively enhance the cognitive skills of Group B children (5-6 years old) at TK IT Al-Fajar Mataram. Cognitive skills, including language, logic, and problem-solving, are essential for early childhood development. Interactive games like Crossword Puzzles are believed to be an engaging and effective approach to stimulate this development. The research employed a Research and Development (R&D) methodology with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. A total of 19 Group B children participated in this study. Research instruments included cognitive skill tests, observation sheets, and feedback questionnaires. The results showed that the educational Crossword Puzzle game was successfully developed and validated by media and material experts. Field trials demonstrated a significant improvement in children's cognitive abilities, particularly in vocabulary recognition, concept comprehension, and simple problem-solving. Children also showed high enthusiasm and interest during gameplay, as reflected in the positive feedback questionnaires. Based on these findings, it can be concluded that the educational Crossword Puzzle game is an effective learning tool for improving the cognitive development of Group B children. This game is recommended as a fun and interactive learning activity at TK IT Al-Fajar Mataram and other early childhood education institutions.